Impact of Ukraina and Russia War Perspective on Islamic Humanitarian Law - Aufa, Al (Faculty of Sharia, IAIN Metro, 2023)
The conflict between Ukraine and Russia has become a global discussion. This conflict has occurred since early 2014 based on the armed conflict in Eastern Ukraine, then coupled with the Crimea crisis and the overthrow of Viktor, which triggered a battle with the Russian government until it was divided into two groups: the pro-EU group and the pro-Russian group. Apart from the crime crisis, on February 24, 2022, the conflict between Russia and Ukraine began again after NATO (North Atlantic Treaty Organization) tried to expand its membership into Eastern Europe by withdrawing Ukraine as a target. The conflict between these two countries, of course, had a significant impact on the global economy. Especially in Indonesia, although it is freely active. Regarding exports, Indonesia experienced a decline in non-oil and gas, then wheat imports, experiencing obstacles, causing an increase in food prices. Therefore, this forced Indonesia to show its attitude towards the conflict between Russia and Ukraine because the effects caused greatly affected various systems in Indonesia. Keywords: war, state,law, Islamic